Application of Western blotting and enzyme linked immunosorbent assay (ELISA) for the diagnosis of Dicrocoelium dendriticum in sheep using excretory secretory (E/S) antigens - Simsek, Sami; Koroglu, Ergun; Utuk, Armagan Erdem (Tubitak Scientific & Technological Research Council Turkey, 2006)
Protein bands of excretory/secretory (E/S) antigens of Dicrocoelium dendriticum were determined using SIDS-PAGE and Western blotting. The E/S antigens were prepared from live adult D. dendriticum, which were obtained from slaughtered sheep at a local abattoir. In the SDS-PAGE analysis of D. dendriticum E/S antigen, 9 protein bands with molecular weights varying between 6 and 66 kDa with Coomassie staining and 14 bands between 6 and 205 kDa with silver staining were detected. Blood samples were obtained from sheep at the local abattoir. Following the examination of the organs for D. dendriticum and other helminths, serum samples were divided into 2 groups as positive (n = 23) and negative (n = 17) for D. dendriticum and the sera were tested using Western blotting. The bands obtained from the sera of positive and negative groups were compared and the molecular weight of specific protein band for D. dendriticum infection was determined as 205 kDa. On the other hand, the ELISA technique was used to study the response of IgG antibodies against E/S antigens of D. dendriticum in the sera of 40 sheep. The sensitivity and specificity of the test were 82.6% and 76.4%, respectively.
Keywords: Dicrocoelium dendriticum; E/S antigen; sheep; Western blotting; ELISA